Pengaruh Penggunaan Medial Arch Support Terhadap Pengurangan Derajat Nyeri, Keseimbangan Statis Dan Activity Of Daily Living Pada Penderita Plantar Faciitis - Dwi Setyawan; Bhisma Murti; Hermanu Joebagio (Jurnal Keterapian Fisik, 2016)
Abstract: Plantar Facitis, Medial Arch Support, Degree Of Pain, Static Balance, Activity Of Daily Living. The case of plantar factis still a lot going on and the handling of the case there are a variety of ways including the use of tools such as the medial arch support, ultrasound therapy, medication, and surgery. The purpose of this study was to analyze the effect of the medial arch support to a reduction in the degree of pain, static balance and activity of daily living in patients with plantar faciitis. This research is kind of Randomized Control Trial (RCT) In this draft, dividing the subjects into two groups. Number of research subjects are 30 subjects were divided into two groups, one group as an experimental group treated medial arch support and one more group as a control group treated with ultrasound (US). Data collection technique used documentation study and observation. Data were analyzed using multiple linear regression analysis and statistical significance of the variables were tested by t test with the results shown by the p value. Significant influence use of medial arch support to the reduction of the degree of pain, static balance and activity of daily living in patients with plantar faciitis. It was demonstrated with p <0.001.